A high frequency model for predicting the behavior of lithium-ion batteries connected to fast switching power electronics. (August 2018) - Korth Pereira Ferraz, Pablo; Schmidt, Robert; Kober, Delf; Kowal, Julia
Highlights: Impedance measurements up to 1 MHz show increasing real part at high frequencies. Semiempirical modeling the behavior at high frequencies with inductive ZARC-elements. Model is suitable for simulating lithium-ion cells connected to power electronics. Abstract: Battery powered energy systems such as electric vehicles utilize power electronics for controlling energy flows between the battery and the load or generation, respectively. Therefore, the battery is under high frequency stress due to fast switching power electronic devices. However, most battery models throughout the literature are not able to cope with high frequency excitation. This paper proposes an easy to implement equivalent circuit model that covers aforementioned frequency regions with a series of inductors that are each connected in parallel with an ohmic resistance. This circuit is parameterized by electrochemical impedance spectroscopy (EIS) up to 100 kHz. For further regions that reach regions of megahertz a skin effect model is investigated and compared to the RL -model. It is shown that such semi-empirical models can be motivated by geometrical considerations that can be found in the literature. Moreover, the proposed model is validated by simulating the voltage response from an input current that originates from an actual back-to-back half bridge DC/DC converter. The promising results indicate that such models might be implemented in future battery energy systems to improve insights on how batteries react to perturbations such as EMI noise or high frequency current ripple.